Diagnostic Accuracy of the Carba NP in Clinical Isolates at a Tertiary Care Centre from Pakistan – a cross sectional study - Farooqui, Fizza; Irfan, Seema (Infectious Diseases Journal of Pakistan, 2022)
Background: The isolation of carbapenem resistant enterobacteriaceae has increased in frequency with time. Rapid detection methods are important for both treatment and infection control purposes. The Carba NP is one such recently developed rapid chromogenic test. This is one of the first studies from Pakistan that assesses the performance of this test in clinical enterobacteriaceae isolates. Results: Fifteen isolates each of carbapenem resistant and sensitive isolates were subjected to testing of minimum inhibitory concentration (MIC) of meropenem and the Carba NP test. Sensitivity and specificity of Carba NP were found to be 100% and 93.3% respectively. Conclusion: The Carba NP is a useful tool for the early detection of carbapenem resistant enterobacteriaceae and activation of infection control response. More studies from the region are needed, especially those that calculate its diagnostic accuracy taking PCR as gold standard so that laboratories can incorporate the test into practice. Keywords: Carba NP, Minimum inhibitory concentration, Carbapenem resistant enterobacteriaceae, Pakistan